The Sasanian Cemetery of Gird-i Bazar in the Peshdar Plain (Iraqi Kurdistan). Issue 1 (2nd January 2022) - Squitieri, Andrea
ABSTRACT: This paper presents the results of the 2015-2017 excavations at the site of Gird-i Bazar in the Sulaymaniyah province of the Kurdish Autonomous Region of Iraq, where the Peshdar Plain Project excavated a Sasanian cemetery installed on the older Iron Age structures of the Dinka Settlement Complex. The characteristics of this cemetery are discussed in the framework of other Sasanian period cemeteries excavated in both Iraq and Iran. The objects from Gird-i Bazar cemetery are presented and compared to other similar items coming from graves and other contexts of the Sasanian period. Particular focus is given to a stamp seal showing a woman figure found in Grave 47, and the results of the radiocarbon analysis on a sample from the same grave, which has provided a good chronological anchor for the cemetery and the stamp seal as well. Finally, a discussion is offered as to the type of community who might have used the cemetery and its possible religious affiliation in relation to the attested presence of Christian communities in northern Mesopotamia during the Sasanian period.